La tipificación de la prisión perpetua en el Estado Ecuatoriano, para las personas que cometan delitos de violación sexual a niñas, niños y adolescentes - Vélez Rubio, Olaf Armando (2015)
The research was conducted based on the facts and statistics that occur each year in the country at a high level of crimes of rape in children and adolescents, it is considered as a form of child abuse, establishing the basic criteria for the classification of crimes as such, the consequences, the psychological damage and the risk of increasing the infringement is established due to the laws and processes that despite being set are not met, however due to the issue raised and acceptance of the proposal by the theme throughout the development of the thesis acceptance of it is given, which is "The introduction of life imprisonment for the crimes of rape in children and adolescents." To reduce this heinous act in this vulnerable group, we must not forget that a law and a well-established process, give a better result to counter crime and especially an investigation of compliance properly, preventing the victim of this crime feel guilty. The main objective of the creation of this law; It is to reduce this type of crime and thereby ensure non-violation of these citizens in their childhood and adolescence. It is for this reason should be punished with the maximum penalty for this kind of offenses and offenders, so is believed to protect the most vulnerable people of Ecuadorian society. We all know that the absence of a law to punish severe and exemplary way, sex offenders commit the crime again, they surely do it again and remain free hurting these defenseless beings which society itself are allowing due not having a law that punishes his heinous crime. We must consider that the worst crime that exists in humanity are the violation of the integrity of a person, specifically sexual, and even worse those committed to children and adolescents. Such violations left marks and a deep wound in emotional life of the victim, By this reason this work is aimed to generate a law that punishes with the highest possible sentence to the offender of this type of crime. Ecuadorian society should not be conformists and accept the laws created only by the Assembly members, we should think that legal professionals can promote the proposal for a law or an amendment be considered, for Assembly Members can know it, analyze it, and discuss it and approval within the National Assembly. Can not believe we did not care what happens around us, perhaps because we have not had one of these reasons, we must take in count that if this would pass us, we surely will wish that be condemned not only by life imprisonment which is what this work intends, but perhaps the death penalty for the offender violator of any of our family, being a child or teenager. Therefore we must denounce crimes, not shut up, even if a relative was who committed it, by shame of society opinion, because if we do not start changing ourselves, will never achieve the goal of reducing this crime in Ecuadorian society